PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP TINGKAT KEPUASAN KONSUMEN (Studi Pada Konsumen Sirup CV Kawista Dewa Burung Rembang) - Awang Ardian Saputra, 15.05.51.0089; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2019)
This study aims to examine the effect of price perception, product quality and promotion on the level of customer satisfaction. The population in this study were consumers who purchased products at CV Kawista Rembang Bird God. Sampling is done by Purposive sampling technique, namely deliberate sampling in accordance with the required sample requirements, the number of samples taken is 100 respondents. The collected data was analyzed using factor analysis to test the validity of statement items, Cronbach alpha to test instrument reliability, and regression analysis to test the effect of the independent variables tested on the level of customer satisfaction. The results of this study indicate that product quality, price perception, and promotion have a positive and significant e,ffect on the level of customer satisfaction on CV Kawista Burung Dewa.